ANALISIS PENGEMBANGAN DAN PRESTASI KERJA PEGAWAI KANTOR CAMAT MERDEKA - ESRA TARIGAN; MILA SARI BR GINTING (LP2MTBM MAKARIOZ, 2023)
Employee development is a capacity building that is applied to employees with the aim of increasing the ability and class promotion at the Merdeka Sub-District Office. In development there is education and training that must be carried out to achieve optimal work performance. In this study using the method of observation and interviews with 16 respondents were analyzed by qualitative descriptive analysis. This study aims to determine whether the development has been carried out well or not in achieving the work performance of the employees of the Independent District Office of Karo Regency. The results of the research obtained at the Independent District Office of Karo Regency indicate that the development has been carried out well although there are still deficiencies that must be improved in the future.